Different Approaches for Catheter Ablation of Para-Hisian Accessory Pathways: Implications for Mapping and Ablation. (June 2017) - Liang, Ming; Wang, Zulu; Liang, Yanchun; Yang, Guitang; Jin, Zhiqing; Sun, Mingyu; Han, Yaling
Abstract : Background—: Catheter ablation of para-Hisian accessory pathways (APs) can be challenging because of adjacent conduction tissue. Some different approaches for ablation, including the inferior vena cava approach (IVC-A), the noncoronary cusp approach (NCC-A), or the superior vena cava approach (SVC-A), have been reported. However, when should para-Hisian APs be mapped and ablated by the IVC-A, NCC-A, or SVC-A is not well established. Methods and Results—: This study included 55 consecutive patients (mean age, 53±11 years, 36 males) with para-Hisian APs. On the basis of the approach resulting in successful ablation, patients were divided into IVC-A, NCC-A, and SVC-A groups. The clinical characteristics, surface ECG, intracardiac electrogram findings, and response to ablation were analyzed. Para-Hisian APs were eliminated by IVC-A in 48 of the 55 (87%) patients. The rates of para-Hisian APs requiring NCC-A (4/55 patients, 7%) and SVC-A (3/55 patients, 6%) were relatively low. During mapping at the para-Hisian region, the local ventricular and atrial potentials were well fused during retrograde AP conduction in 45 of the 48 patients in IVC-A group, 0 of the 4 patients in NCC-A group, and 1 of the 3 patients in SVC-A group, respectively. There was no significant difference in the preexcitation characteristics among the 3 groups. Conclusion—: Most para-Hisian APs can be safely and effectively ablated by IVC-A, and ablation in the NCC is not an initial or a preferred approach. The degree of local ventriculoatrial fusion in the para-Hisian region during retrograde AP conduction can differentiate or predict the successful ablation site.